Trazodone effectiveness in depression: impacts of trazodone extended release vs SSRIs on the health status and quality of life of patients with major depressive disorder - Siwek, Marcin; Chrobak, Adrian Andrzej; Krupa, Anna Julia; Gorostowicz, Aleksandra; Juryk, Andrzej; Dudek, Dominika (Frontiers in Pharmacology, 2025)
IntroductionEarly research on the pharmacotherapy for major depressive disorder (MDD) has largely focused on symptomatic improvements, whereas this focus has shifted to functioning and quality of life in recent years. Studies have confirmed that antidepressants generally improve the functional outcomes in MDD, but very few works have compared the efficacies of specific drugs. The present work aims to compare the impacts of trazodone once-a-day extended-release (XR) vs selective serotonin reuptake inhibitors (SSRIs) on the health status and quality of life in MDD.MethodsData were gathered from 180 subjects through a naturalistic observation study of trazodone effectiveness in depression (TED) and analyzed. The TED study participants received trazodone XR of SSRIs in flexible doses for 12 weeks. The health status and health-related quality of life (HRQoL) were evaluated using the EQ-5D-5L tool at baseline as well as 2, 4, 8, and 12 weeks.ResultsAt baseline, the subjects treated with trazodone XR vs SSRIs presented similar health status profiles and HRQoL values with respect to the mobility, self-care, and anxiety/depression dimensions along with lower scores for the usual activities, pain/discomfort, overall HRQoL, and health status. Both trazodone XR and SSRIs improved the health status and HRQoL of the MDD patients at all subsequent timepoints. Compared to SSRIs, trazodone XR provided greater improvements in terms of the self-care, usual activities, pain/discomfort, and anxiety/depression measures and more often improved participant overall health status and HRQoL. More participants reported mixed changes in their health status and HRQoL in the SSRI group than the trazodone XR group.DiscussionHealth status and HRQoL improved in both treatment arms, with preferable scores in trazodone XR vs. SSRIs group.